PENGHAYATAN KETUHANAN MENURUT ALIRAN KEBATINAN PAGUYUBAN SUMARAH - Saputro, Fendi Gatot (Jurnal Filsafat "WISDOM", 2009)
AbstractWhat philosophers observe, it also becomes an interest formost people, is reaching the truth, and it covers various questions raising in human minds. According to mystic of Paguyuban Sumarah, existence of God is a private and personal experience. It means human can meet God. Therefore, it is needed a way or method, namely Sujud Sumarah.Paguyuban Sumarah is an organized mystical divinity groupthat has teachings, such as â€œManunggaling Kawula lan Gustiâ€ and â€œJumbuhing Kawula lan Gustiâ€. The teachings can be practiced by doing â€œSujud Sumarahâ€. â€œSujud Sumarahâ€ is a way to know the Truth essence by bowing motionless silently, uniting the â€œtrimurtiâ€ (imagination, sense or feeling, and mind) where its direction is in the middle of chest through stages of â€œeneng, ening, elingâ€. The Paguyuban Sumarah understands God as an immanent and transcendent being, and professes the ideology of monotheistic monism: there is only one Truth, God, the Great Unity, the One; God as the Absolute Substance, and the basic of all things, the One Origin of Mind and Body, Spiritual and Body; and God is different from all creatures and creations (a dichotomy).Keyword: Paguyuban Sumarah, Sujud Sumarah, MonotheisticMonism, Immanent-Transcendent, ManunggalingKawula Lan Gusti, Jumbuhing Kawula Lan Gusti.